Dietary behaviours in the context of nutrition transition: a systematic review and meta-analyses in two African countries. Issue 11 (11th August 2020) - Rousham, Emily K; Pradeilles, Rebecca; Akparibo, Robert; Aryeetey, Richmond; Bash, Kristin; Booth, Andrew; Muthuri, Stella K; Osei-Kwasi, Hibbah; Marr, Colette M; Norris, Tom; Holdsworth, Michelle
Abstract: Objective: To synthesise evidence of urban dietary behaviours (macronutrients, types of foods, dietary diversity and dietary practices) in two African countries in relation to postulated changes in the context of nutrition transition. Design: Systematic review and meta-analyses, including six online databases and grey literature, 1971–2018 (Protocol CRD42017067718). Setting: Urban Ghana and Kenya. Participants: Population-based studies of healthy adolescents and adults. Results: The forty-seven included studies encompassed 20 726 individuals plus 6526 households. Macronutrients were within WHO-recommended ranges: mean energy intake was 1867 kcal/d (95 % CI 1764, 1969) and the proportions of macronutrients were carbohydrate 61·2 % (58·4, 64·0), fat 25·3 % (22·8, 28·0) and protein 13·7 % (12·3, 15·1). The proportion of population consuming fruit and vegetables was 51·6 %; unhealthy foods, 29·4 %; and sugar-sweetened beverages (SSBs), 39·9 %. Two-thirds (68·8 %) consumed animal-source proteins. Dietary diversity scores were within the mid-range. Meal patterns were structured (typically three meals per day), with evidence lacking on snacking or eating out. Conclusions: Population-level diets fell within WHO macronutrient recommendations, were relatively diverse with structured meal patterns, but some indications of nutrition transition were apparent. The proportion of population consuming fruit and vegetables was low compared to healthy-eating recommendations, and consumption of SSBs was widespread. A paucity of evidence from 1971 to 2010 precluded a longitudinal analysis of nutrition transition. Evidence from these two countries indicates which aspects of dietary behaviours may be contributing to increasing overweight/obesity, namely a low proportion of population consuming fruit and vegetables and widespread consumption of SSBs. These are potential targets for promoting healthier diets.